Comparing use and acceptability of menstrual cups and sanitary pads by schoolgirls in rural Western Kenya - Mason, Linda; Nyothach, Elizabeth; van Eijk, Anna Maria; Obor, David; Alexander, Kelly T.; Ngere, Isaac; Laserson, Kayla; Phillips-Howard, Penelope (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Girls in low and middle-income countries (LMIC) lack access to hygienic and affordable menstrual products. We explore Kenyan schoolgirls’ use and views of the cup compared to girls provided with disposable sanitary pads for a feasibility study. Methods: Schoolgirls aged 14-16 years, received a menstrual cup in 10 schools or 16 pads/month in another10 schools. All were trained by nurses on puberty, hand washing, and product use. They self-completed a net book survey at baseline and twice a term during a year follow-up. We examined their reported ease of insertion and removal, also comfort, soreness, and pain with product use. An aggregate ‘acceptability’ score was compiled for each product and girls’ socio-demographic and menstrual characteristics were compared. Results: 195 participants received cups and 255 pads. Mean age was 14.6 years, menarchial age was 13.6 years, with an average 3.8 days menses per month. Cup use was 39% in month 1, rising to 80% by month 12 (linear trend p<0.001). Pad use rose from 85% to 92% (linear trend p=0.15). Measures of cup acceptability demonstrated girls had initial problems using the cup but reported difficulties with insertion, removal and comfort reduced over time. Girls using pads reported fewer acceptability issues. At baseline, approximately a quarter of girls in the pad arm reported inserting pads intravaginally although this was significantly lower among girls with prior experience of pad use (aRR 0.62; 0.45-0.87). Conclusions: While a smaller proportion of girls provided with cups used them in the first months compared to girls given pads, reported use was similar by study-end, and early acceptability issues reduced over time. Girls in LMIC may successfully and comfortably use cups, but require instruction, support and some persistence.